Japan Administered Account for Selected IMF Activities (JSA) : Annual Report for Fiscal Year 2004. (International Monetary Fund, 2005)
This paper reports a brief description of the IMF and its activities, focusing in particular on its technical assistance activities. The report describes in detail the Japan Administered Account for Selected Fund Activities (JSA)-its objectives, size, scope and use, as well as assessments of its activities, with a focus on fiscal year 2004-and the scholarship programs that it finances. The IMF finances its technical assistance for its member countries mainly from its own budgetary resources; it also receives external financing from bilateral and multilateral partners. JSA resources can be used to cover the costs of short- and long-term technical assistance experts and those providing seminars and workshops. In addition, JSA projects in two or three countries are visited and reviewed each year by a joint Japan-IMF mission. These visits provide the Japanese authorities with a firsthand view of how JSA funding is being used in the field.